Exploring Pre-service Teachers’ TPACK Development and Academic Integrity Using ChatGPT - Saputra, Dewa Ngakan Made Guna; Kusuma, I Putu Indra; Indrayani, Luh (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
The rapid development of Generative Artificial Intelligence (GenAI), particularly ChatGPT, has transformed educational practices and created both opportunities and challenges in teacher education. This study explores how pre-service EFL teachers use ChatGPT to develop their Technological Pedagogical Content Knowledge (TPACK) while maintaining academic integrity during teaching practice. Employing a sequential explanatory mixed-methods design, the research involved 100 survey respondents and 10 interview participants from Universitas Pendidikan Ganesha, Bali. Data were collected through questionnaires and semi-structured interviews and analyzed using descriptive statistics and thematic analysis. The results revealed that pre-service teachers frequently used ChatGPT to explore digital tools, design lesson plans, and create interactive learning activities, indicating that ChatGPT functions as a pedagogical partner in supporting TPACK integration. Moreover, the findings showed that pre-service teachers demonstrated strong awareness of ethical principles in AI use by paraphrasing, modifying, and verifying AI-generated content to ensure originality and avoid plagiarism. These practices reflect their ability to balance innovation with responsibility in digital learning environments. The study concludes that integrating AI literacy and ethical reflection into teacher education curricula is essential to prepare pre-service teachers as adaptive, reflective, and integrity-driven educators in the era of artificial intelligence.